Analysis of Market Access Agreements in Turkey - Kockaya, Guvenc; Atalay, Okan; Kurnaz, Mustafa; Okcun, Selin; Sencan, Nazlı; Gedik, Cigdem; Saylan, Mete; Oguzhan, Gulpembe (Farmeconomia. Health economics and therapeutic pathways, 2020)
BACKGROUND: Reimbursement agencies are increasingly adopting innovative reimbursement approaches for new and expensive technologies. Social Security Institution (SSI), Turkey`s reimbursement agency, established the Alternative Reimbursement Commission (ARC) on February 10, 2016. This study aimed to understand the implementations of market access agreements in recent years in Turkey. METHODS: Decisions of the Health Services Pricing Commission published in the official gazette , and information from the Turkey Pharmaceuticals and Medical Devices Agency, the Abroad Drug List, Health Implementation Communique published by SSI with additional lists, such as the Annex-4A List of Reimbursed Medicines and the Annex-4C Abroad Drug Price List, were used. The data was transferred to Windows Office Excel files, and a descriptive analysis was conducted and evaluated by two market access experts. RESULTS: There were 57 drugs included in the coverage of reimbursement with alternative reimbursement since the application was started in Turkey. 35 of them were added to Annex-4A and 22 of them to Annex-4C. Furthermore, 45.6% of the drugs had an Anatomic Therapeutic Chemical Classification (ATC) code of l-antineoplastic and immunomodulating agents, 28% were orphan drugs, 44 of them had a confidential discount rate, and financial-based agreement models were preferred for nearly all agreements. CONCLUSIONS: Turkey has been implementing market access agreements since mid-2016. In the past 3 years, 57 drugs have been covered for reimbursement under the new implementation. Further analysis should be conducted to understand the decision-making process involved.